2004
DOI: 10.1152/ajpheart.00829.2003
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the chronic severely failing ischemic sheep heart after coronary microembolization: functional, energetic, structural, and cellular responses

Abstract: The mandatory use of pharmacotherapy in human heart failure (HF) impedes further study of natural history and remodeling mechanisms. We created a sheep model of chronic, severe, ischemic HF [left ventricular (LV) ejection fraction (LVEF) <35% stable over 4 wk] by selective coronary microembolization under general anesthesia and followed hemodynamic, energetic, neurohumoral, structural, and cellular responses over 6 mo. Thirty-eight sheep were induced into HF (58% success), with 23 sheep followed for 6 mo (21 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
(44 reference statements)
0
29
0
2
Order By: Relevance
“…19 The effects of BRL37344 (BRL) on standard hemodynamic variables and LV end-systolic pressurevolume relationships (ESPVRs) of continuous LV pressure-volume loops were determined at baseline and after induction of heart failure. Because ESPVR is relatively load independent, it was chosen a priori as the primary index of cardiac contractility.…”
Section: Heart Failure Model and In Vivo Studies Of Cardiac Contractimentioning
confidence: 99%
See 1 more Smart Citation
“…19 The effects of BRL37344 (BRL) on standard hemodynamic variables and LV end-systolic pressurevolume relationships (ESPVRs) of continuous LV pressure-volume loops were determined at baseline and after induction of heart failure. Because ESPVR is relatively load independent, it was chosen a priori as the primary index of cardiac contractility.…”
Section: Heart Failure Model and In Vivo Studies Of Cardiac Contractimentioning
confidence: 99%
“…19 Expression of the ␤ 3 AR in sheep heart was ascertained by immunoblotting. Myocardium from wild-type and ␤ 3 AR Ϫ/Ϫ mouse as positive and negative controls ( Figure 7A).…”
Section: Effects Of Brl On Contractility Of the Normal And Failing Heartmentioning
confidence: 99%
“…However, subsequent studies revealed limitations to this simplified theory, such as ESPVR curvilinearity, afterload dependence under certain conditions, and that V o may change during contraction (18,26,29). Furthermore, the ESPVR has been reported to be influenced by regional ischemia in acute and chronic animal models of heart failure (13,21) and augmented in spontaneously hypertensive rats (5).…”
Section: The Use Of Time-varying Elastance For Assessing Cardiac Funcmentioning
confidence: 99%
“…In addition, the trauma may render successful recovery from anesthesia in models of myocardial infarction more difficult, compared with closed chest procedures. Besides, to date, there are various myocardial ischemic animal models, such as ligating the coronary artery (Takahashi et al, 2005), placing constrictors on the coronary artery (Laham et al, 2000), putting microembolus into the coronary artery (Huang et al, 2004), or injecting ferric chloride via the vein (Dogne et al, 2005). However, operations in these methods lead to much damage in animals, and channelization can not be restored in the obstructed coronary artery.…”
Section: Acute Ischemic and Reperfusion Animal Modelsmentioning
confidence: 99%